Optimizing Coastal Management: A Comprehensive Value Chain Analysis Approach for Sustainable Economic Development in Java, Indonesia - Zuhud Rozaki; Ahmad Shabudin Ariffin; Mona Fairuz Ramli; Elvina Nurrohma; Novara Nurvinka Ramadhani; Winda Ismah Setyoasih; Masateru Senge (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract